The Financial Literacy and Simple Bookkeeping Training for Micro, Small and Medium Enterprises in Mattirotasi Village - Husain, Saddan; sahara, Ira (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
Micro, Small and Medium Enterprises are the drivers of the people's economy. In a number of conditions, MSMEs are the wheels of economic rotation for the Indonesian nation. The MSME development strategy is needed so that the business being carried out progresses. If no strategy is used, it can result in the business being run in place, initiative is an answer for a change both in terms of administration and product promotion. Of course it will be an interesting concern if strengthening the economy will further strengthen the people-based economy. The service method uses Community Based Research (CBR) which is a service model that prioritizes community needs and actively conducts research that combines various elements of society to answer challenges that arise within the community itself. The result of this service is that the community understands the importance of simple bookkeeping in developing a business or business being run. Direct practice in the dedication process becomes an integral part of the dedication implementation process. In addition, the support from the Mattirotasi village government was extraordinary, as evidenced by its involvement in the community service process.